Stabilisation of oil-contaminated soils using microbially induced calcite crystals by bacterial flocs - Cheng, L.; Shahin, Mohamed (ICE PUBLISHING, 2017)
Of late, oil spills have occurred frequently in many places around the world, causing serious geoenvironmental problems. The oil products adversely affect the safety of civil engineering infrastructures by altering the engineering properties of soils. This study proposes and describes a new approach for the stabilisation of oil-contaminated soils using a modified approach for the microbially induced calcite precipitation (MICP) technique. In contrast to one common method of MICP treatment that has been applied in the literature through the two-phase injection method, the new approach proposed herein involves premixing ureolytic bacterial flocs with oil-contaminated soils for the purpose of bacteria introduction and fixation. Repeated flushes of cementation solution (i.e. calcium chloride and urea) are then followed, leading to the precipitation of low-soluble calcite (calcium carbonate) crystals. This new MICP exploration was successful in producing an unconfined compressive strength of up to 1200 kPa, thereby providing a high potential for stabilising oil-contaminated soils in regions of oil spills.